Recent progress of tunnel junction-based ultra-violet light emitting diodes. (29th May 2019) - Zhang, Yuewei; Jamal-Eddine, Zane; Rajan, Siddharth
Abstract: AlGaN-based UV LEDs are promising for a wide range of industrial, household and healthcare applications. However, widespread adoption of UV LEDs is limited by the poor device efficiency. This has been attributed to the strong internal light absorption and poor electrical injection efficiency associated with the conventional UV LED structures, which typically use an absorbing p-GaN layer for p-type contact. Recent development of ultra-wide bandgap AlGaN tunnel junctions enabled a novel UV LED design with the absence of the absorbing p-GaN contact layer. In this work, we review the recent progress of AlGaN tunnel junctions and the development of tunnel junction-based UV LEDs, and discuss the challenges and future perspectives for the realization of high power, high efficiency UV LEDs.